Representasi Pesan Moral Dalam Film ”Pertaruhan” (Semiotika Charles Sanders Peirce) - Fahreyza, Muhamad; Fajar Wulandari, Yulianti; Imron, Ali (Brand Communication, 2025)
Film is a form of art and media that enjoys a high level of popularity and serves as a means of entertainment, education, and information. Through films, audiences not only seek enjoyment but also gain new insights and knowledge. Although many people watch films primarily for leisure, each storyline often contains profound meanings and moral messages that can be taken as life lessons. One such film that conveys these values is Pertaruhan, which is the subject of this research. The purpose of this study is to explore the representation of moral messages in the film Pertaruhan using Charles Sanders Peirce’s semiotic theory, which includes three main components: sign, object, and interpretant. This research employs a descriptive qualitative method, with data collected through observation and documentation of the film. The results of the study indicate that there are eight scenes that explicitly represent moral messages, ultimately providing a deeper understanding of the life values conveyed through the film.